2005
DOI: 10.1111/j.1471-8286.2005.00998.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite DNA markers for delineating population structure and kinship among the endangered Kirtland's warbler (Dendroica kirtlandii)

Abstract: We document the isolation and characterization of 23 microsatellite DNA markers for the endangered Kirtland's warbler (Dendroica kirtlandii), a Nearctic/Neotropical migrant passerine. This suite of markers revealed moderate to high levels of allelic diversity (averaging 7.7 alleles per locus) and heterozygosity (averaging 72%). Genotypic frequencies at 22 of 23 (95%) markers conformed to Hardy–Weinberg equilibrium expectations, and no linkage disequilibrium was observed in blood samples taken from 14 warblers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Dried samples found application in populational genetics studies as a convenient instrument of sample collection and investigation (Sacks et al 2004 ; Silva et al 2009 ; Lall et al 2010 ; Kraus et al 2013 ; Guerrini et al 2014 ; Kashiwagi et al 2015 ; Nunziata et al 2016 ). Isolation and characterization of DNA microsatellite markers, their genotyping for population genetic studies was also described in other works (Sacks et al 2004 ; King et al 2005 ; Lucentini et al 2006 ; Carr and Appleyard 2008 ; Heim et al 2012 ; Nunziata et al 2016 ). Kashiwagi et al ( 2015 ) originally described an underwater collection of manta ray mucus by SCUBA divers for further application on FTA Elute cards for population genetic studies.…”
Section: Dbs Samples In Veterinary Medicine and Animal Biology: Diagn...mentioning
confidence: 87%
See 1 more Smart Citation
“…Dried samples found application in populational genetics studies as a convenient instrument of sample collection and investigation (Sacks et al 2004 ; Silva et al 2009 ; Lall et al 2010 ; Kraus et al 2013 ; Guerrini et al 2014 ; Kashiwagi et al 2015 ; Nunziata et al 2016 ). Isolation and characterization of DNA microsatellite markers, their genotyping for population genetic studies was also described in other works (Sacks et al 2004 ; King et al 2005 ; Lucentini et al 2006 ; Carr and Appleyard 2008 ; Heim et al 2012 ; Nunziata et al 2016 ). Kashiwagi et al ( 2015 ) originally described an underwater collection of manta ray mucus by SCUBA divers for further application on FTA Elute cards for population genetic studies.…”
Section: Dbs Samples In Veterinary Medicine and Animal Biology: Diagn...mentioning
confidence: 87%
“…The authors concluded that preservation FTA cards were not adequate for providing unfragmented DNA for downstream genomic applications such as microsatellite and genomic sequencing especially for mammals which have non-nucleated blood cells. However, other researches successfully used FTA cards for genetic applications such as microsatellite genotyping (King et al 2005 ; Lucentini et al 2006 ; Carr and Appleyard 2008 ; Heim et al 2012 ; Nunziata et al 2016 ). For example, Lucentini et al ( 2006 ) described a nondestructive method for obtaining the high-quality DNA from fish body mucus and buccal cells, making it the best choice for populational genotyping.…”
Section: Carriers For Dried Samples and Sample Pretreatmentmentioning
confidence: 99%
“…; King et al . ). For each locus, GenBank accessions were assigned chromosome locations in the zebra finch genome assemblies Taeniopygia_guttata ‐3.2.4 (v 1.1), by performing a blat (Kent ) search using the ensembl webpage (http://www.ensembl.org/Multi/blastview).…”
Section: Methodsmentioning
confidence: 97%
“…We used 17 microsatellite loci (Table 2 ), 12 of these loci were developed specifically for Kirtland’s warblers [ 44 ]. Five other loci Dpu16 [ 45 ], Lswu07 [ 46 ] and Vecr04, Vecr08, Vecr10 were developed for other species [ 47 ].…”
Section: Methodsmentioning
confidence: 99%